Ravines Erosion Problem in Dhaulpur District, Rajasthan, India - Singh, Rani (National Geographical Journal of India, 2022)
In India vast tracks of lands (20.17% of total geographical area) exists as wastelands. In Thar Desert region of Rajasthan, land degradation is occurring at an increasing rate. The region contains more than 2lacs sq. kms of arid land has a fast growing human population and increasing livestock number, all of which accelerate damage to fragile arid landscape. Soil and gully erosion have caused major environmental disasters worldwide. Many urban and rural communities have been severely affected, while the sustainability of the total landscape has been threatened. The present study juxtaposes the view of land degradation with the increase in wasteland especially focused on gullies/ravenous land, in eastern most part of Rajasthan where whole economy is dependent on agriculture. Here, land degradation is a dominant problem. Over 40% area is affected by various categories of wasteland. Gully and ravine erosion is severe problem along the river Chambal (only perennial river in state), which has a calamitous effect on the agro-economical activities of the area. In addition to this, salinity and degradation of forest are other problems causing degradation of land. Government officials and committees should be constituted at village level to undertake wasteland developmental planning with the involvement of village, block and district level officials and are also required to assist the farmers. Yes, efforts are needed for bringing out sustainable management planning that provides the clear insight into the real need of our people.